‘If I’m not police, then who am I?’: About belonging and identity in the police - Filstad, Cathrine (International journal of police science & management, 2022)
This article investigates senses of belonging and the interrelation between belonging and identity in policing. We use Snap Log images and text of police leaders’ own interpretations of belonging at work. Belonging is relational, cultural, material and embedded in collective engagement, and is about being equals where everyone contributes. Engagement creates a strong emotional attachment to an idea of ‘us’ and of being part of something bigger than oneself. Belonging represents imaginations of the police mission and being proud to be part of that. It is about the ‘here and now’ and about taking care of each other when things are tough. The link between belonging and identifying with policing is further amplified through materiality and symbols, as commonly used in police leaders’ images. The sense of belonging to the police when wearing the same uniform and using the same artefacts and symbols becomes important for a person’s identity as a police officer.